MicroRNAs as Immunotherapy Targets for Treating Gastroenterological Cancers. (26th June 2018) - Yang, Yixin; Alderman, Christopher; Sehlaoui, Ayoub; Xiao, Yuan; Wang, Wei
Abstract : Gastroenterological cancers are the most common cancers categorized by systems and are estimated to comprise 18.4% of all cancers in the United States in 2017. Gastroenterological cancers are estimated to contribute 26.2% of cancer-related death in 2017. Gastroenterological cancers are characterized by late diagnosis, metastasis, high recurrence, and being refractory to current therapies. Since the current targeted therapies provide limited benefit to the overall response and survival, there is an urgent need for developing novel therapeutic strategy to improve the outcome of gastroenterological cancers. Immunotherapy has been developed and underwent clinical trials, but displayed limited therapeutic benefit. Since aberrant expressions of miRNAs are found in gastroenterological cancers and miRNAs have been shown to regulate antitumor immunity, the combination therapy combining the traditional antibody-based immunotherapy and novel miRNA-based immunotherapy is promising for achieving clinical success. This review summarizes the current knowledge about the miRNAs and long noncoding RNAs that exhibit immunoregulatory roles in gastroenterological cancers and precancerous diseases of digestive system, as well as the miRNA-based clinical trials for gastroenterological cancers. This review also analyzes the ongoing challenge of identifying appropriate therapy candidates for complex and dynamic tumor microenvironment, ensuring efficient and targeted delivery to specific cancer tissues, and developing strategy for avoiding off-target effect.